Meta-Analysis the Effect of Prenatal Yoga to Lower Anxiety and Stress in Intrapartum Women - Wulandari, Adetya; Prasetya, Hanung; Murti, Bhisma (Journal of Maternal and Child Health, 2022)
Background: Pregnant women are very susceptible to complications or high risk during pregnancy, especially before delivery, causing anxiety and stress. Prenatal yoga is known to relax breathing which can relax muscles and reduce anxiety. The purpose of this study was to analyze the effect of prenatal yoga on pregnant women on anxiety and stress in the face of labor. Subjects and Method: This study was a meta-analysis with the following PICO, population: pregnant women. Intervention: prenatal yoga. Comparison: not doing prenatal yoga. Result: reduced stress and anxiety. Keywords to search for articles “Prenatal Yoga” OR “Pregnancy yoga” AND “Anxiety” AND “Stress” AND “randomized controlled trial”. The articles included are full-text English and a randomized controlled trial study design from 2009-2021. Article selection is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 12 RCT studies from the Asian, American and European continents were selected for systematic review and meta-analysis. Based on 9 articles stated that pregnant women who do prenatal yoga can reduce anxiety about childbirth by 0.86 times compared to not doing prenatal yoga (SMD = -0.86; 95% CI -1.50 to -0.21; p= 0.010) and 5 articles state that pregnant women those who do prenatal yoga can reduce stress during childbirth by 1.23 times compared to those who do not do prenatal yoga (SMD= -1.23; 95% CI= -1.59 to -0.87; p< 0.001). Conclusion: Prenatal yoga can reduce anxiety and stress in pregnant women in the face of childbirth. Keywords: anxiety, stress, pregnancy, prenatal yoga Correspondence: Adetya Wulandari. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Mobile: 081274814357. Email: Adetya1507@gmail.com.